Transaksi Rahn Emas Dalam Tinjauan Tafsir dan Hadis - Dedy Setiawan; Ahmad Hasan Ridwan (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
Gold is one of the instruments that is most in demand by the Indonesian people because it has a stable value and a liquid commodity, on this basis it makes more and more institutions that have financing products with gold pawn schemes. The purpose of this study was to determine the transaction of rahn gold in the review of interpretations and hadiths. The type of research used in the research on Rahn Emas Transactions in the Review of Tafsir and Hadith is Library Research, which is a research method that obtains data by studying, researching, and reviewing related library materials, as well as examining data by observing phenomena that occur in the field. The result of the review of interpretations and hadiths about gold is that the transaction of rahn gold is lawful based on the Word of God, QS. al-Baqarah [2]: 283:, Hadith of the Prophet narrated by al-Bukhari and Muslim from 'A'isha ra, Hadith of the Prophet narrated by al-Shafi'i, al-Daraquthni and Ibn Majah from Abu Hurairah, Hadith of the Prophet narrated by the Jama'ah , except for Muslims and al-Nasa'i, the Ijma ulama in the book (al-Zuhaili, al-Fiqh al-Islami wa Adillatuhu, 1985, V: 181) and is supported by fiqh rules, namely Basically all forms of muamalat can be done unless there is evidence which forbids it. The study of the meaning of mufradat as an order if they are in debt or muamalah within a certain period of time there must be a written agreement and bring witnesses. Transactions carried out in rahn gold are a) the costs and costs of storing goods (marhun) are borne by the pawnbroker (rahin), b) the costs borne by the pawnbroker are adjusted to the expenditure of rahin, and c) the cost of storing goods (marhun) is carried out based on an ijarah agreement.